Diverted total syntheses of potent cell adhesion inhibitor peribysin E analogues - Handore, Kishor L.; Reddy, D. Srinivasa (Organic Letters, 2013)
Preliminary results from a program aimed at the creation of a focused library of analogues around the natural product peribysin E, a potent biologically active and structurally fascinating molecule, are reported. The total synthesis of (+/-)-peribysin E was accomplished using a short route. Eight new analogues of the natural compound have been accomplished by means of ``diverted total synthesis'' in less than 10 steps. The present effort highlights protecting-group-free total syntheses and the shortest route to access these functionally embellished hydrindanes.

Total synthesis of (+/-)-nardoaristolone B and its analogues - Handore, Kishor L.; Reddy, D. Srinivasa (Organic Letters, 2014)
The first total synthesis of nardoaristolone B, a nor-sesquiterpenoid with an unusual fused ring system and having protective effects on the injury of neonatal rat cardiomyocytes, has been accomplished. Stereoselective synthesis of its novel analogues inlcuding exo-cyclopropyl ring fusion is also part of this disclosure. In addition, an alternate and more efficient one-step method to make a 3/5/6 tricyclic ring system using the Robinson annulation method has been developed toward the generation of a library of compounds around this skeleton.

Total syntheses and biological evaluation of (+/-)-botryosphaeridione, (+/-)-pleodendione, 4-epi-periconianone B, and analogues - Handore, Kishor L.; Jadhav, Prakash D.; Hazra, Bibhabasu; Basu, Anirban; Reddy, D. Srinivasa (ACS Medicinal Chemistry Letters, 2015)
The total syntheses of (+/-)-botryosphaeridione, (+/-)-pleodendione, (+/-)-hoaensieremodione, 4-epi-periconianone B, and their analogues have been accomplished for the first time. All the synthesized target compounds were screened in neural anti-inflammatory assays using LPS induced microglia cells (N9). Among them, compounds 1 and 21 were identified as potential lead compounds for further profiling.
Keywords: antineuroinflammatoty agents; bohyosphaeridione; Natural product; pleodendione; Total synthesis

Identification of noreremophilane-based inhibitors of angiogenesis using zebrafish assays - Muthukumarasamy, Kalai Mangai; Handore, Kishor L.; Kakade, Dipti N.; Shinde, Madhuri V.; Ranjan, Shashi; Kumar, Naveen; Sehrawat, Seema; Sachidanandan, Chetana; Reddy, D. Srinivasa (Organic & Biomolecular Chemistry, 2016)

Solution-phase synthesis of the macrocyclic core of teixobactin - Dhara, Santu; Gunjal, Vidya B.; Handore, Kishor L.; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2016)
Towards the total chemical synthesis of the exceptionally potent antibiotic teixobactin, we synthesized the macrocyclic core of a natural product by using a solution-phase approach. The gramscale synthesis of L-allo-enduracididine and Shiina macrolactonization are highlights of the present disclosure.

Total synthesis of (-)-nardoaristolone B - Ople, Rohini S.; Handore, Kishor L.; Kamat, Nidhi S.; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2016)
A stereoselective total synthesis of (-)-Nardoaristolone B, a nor-aristolane sesquiterpenoid natural product with an unusual 3/5/6 tricyclic ring system is described. The highlights of the present work includes use of (+)-(R)-Pulegone as a chiral-pool starting material, ring-closing metathesis, allylic oxidation and stereoselective cyclopropanation. In addition, a new analogue of Nardoaristolone B (minor product from the final step) was isolated in pure form and fully characterized with the help of single-crystal X-ray analysis.
Keywords: Chiral pool; cyclopropanation; Nardoaristolone B; Natural products; Total synthesis

Access to fused tricyclic gamma-butyrolactones, a natural product -like scaffold - Kalmode, Hanuman P.; Handore, Kishor L.; Reddy, D. Srinivasa (Journal Of Organic Chemistry, 2017)
Serendipitous findings of an acid mediated skeletal rearrangement of bicydo-beta-ketoester having cyclopropyl ring to access fused tricyclic gamma-butyrolactones has been described. This novel transformation has been optimized to 30 mol% p-toluenesulfonic acid (p-TSA) in toluene using Dean Stark apparatus, where the aldol condensation, cyclopropyl ring opening followed by cyclization took place in a single-pot operation. The resulting tricyclic compounds are interesting chemotype with natural product resemblance and may find useful applications in the future.

Total synthesis and biological evaluation of cell adhesion inhibitors peribysin A and B: structural revision of peribysin B - Kalmode, Hanuman P.; Handore, Kishor L.; Rajput, Raveena; Shaikh, Samir R.; Gonnade, Rajesh G.; Kulkarni, Kiran A.; Reddy, D. Srinivasa (Organic letters, 2018)
Total synthesis of potent cell-adhesion inhibitors peribysins A and B has been accomplished for the first time in racemic form. A Diels-Alder/aldol sequence to build the skeleton and decoration of the desired functionalities of the targeted natural products using highly stereoselective operations are the highlights. The structures of synthesized peribysins were fully characterized using spectral data and single-crystal X-ray analysis. Through this total synthesis, the initially proposed structure of peribysin B has been revised. Furthermore, the cell-adhesion inhibition potential of the scaffold (two peribysins + three analogues) was confirmed using anti-adhesion assay.

Neural anti-inflammatory natural product periconianone A: total synthesis and biological evaluation - Kalmode, Hanuman P.; Patil, Suhag S.; Handore, Kishor L.; Athawale, Paresh R.; Dandela, Rambabu; Verma, Abhishek Kumar; Basu, Anirban; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2019)
Total synthesis of periconianone A, an eremophilane-type sesquiterpenoid with impressive neural anti-inflammatory potential, has been accomplished. Diels-Alder/aldol strategy to construct tetrahydro-naphthalene-2,6-dione scaffold, allylic oxidation of dienone using DBU/O-2 and postulated biomimetic aldol reaction to construct 6/6/6 tricyclic system are the highlights of the present synthesis. Furthermore, the synthesized (+/-)-periconianone A and two close analogs were tested for their neural anti-inflammatory activity using various assays. In the course of our study we found a structurally simplified analog is superior to (+/-)-periconianone A.
Keywords: Aldol; Allylic oxidation; Biological evaluation; Cytotoxicity; Diels-Alder; Periconianone A

Highly stereoselective diels-alder-based strategy for the synthesis of 3-epi-formicin A and 1-epi-formicin B - Khamkar, Sunil L.; Handore, Kishor L.; Shinde, Harish M.; Reddy, D. Srinivasa (Organic Letters, 2024)
The first enantioselective approach based on a highly stereoselective Diels-Alder reaction for the synthesis of 3-epi-formicin A and 1-epi-formicin B with rare N-acetylcysteamine-containing indenone thioesters is reported. The strategy utilizes a key Diels-Alder reaction to form the core hydrindane system with three contiguous stereocenters in very high levels of diastereo- and regioselectivity and one-pot oxidation/isomerization/dehydrogenation. The scope of this method was tested with different substrates to give cycloadducts in a highly diastereoselective manner.

Diastereoselective synthesis of cyclic and spirocyclic quaternary carbons via iron-catalyzed ring contraction of cyclic ketones: a formal synthesis of perhydrohistrionicotoxin - Survase, Vijayanand U.; Rokade, Avinash D.; Handore, Kishor L. (Organic Letters, 2025)
The iron-catalyzed hydrogen atom transfer (HAT)-initiated Dowd-Beckwith rearrangement presents a new approach for synthesizing cyclic and spirocyclic quaternary carbons from readily available beta-keto esters and cyclic diketones with high yields. This reaction proceeds in a stereocontrolled manner, enabling the formation of synthetically valuable cyclic ketones with two contiguous stereocenters, including quaternary centers. This transformation introduces an innovative bond disconnection strategy for ring-contraction reactions. Additionally, a short formal synthesis of perhydrohistrionicotoxin was efficiently achieved using this methodology.

Efficient synthesis of functionalized alkylidenephthalides, butenolides, pyranones, and isocoumarins via I2-PPh3: synthesis of Thunberginols A and F - Abhang, Rohitkumar V.; Bhagwat, Prathamesh N.; Handore, Kishor L. (Organic & Biomolecular Chemistry, 2025)
A simple and efficient synthesis of functionalized alkylidenephthalides, butenolides, pyranones, and isocoumarins was achieved using I2-PPh3-Et3N reagent combination. The products obtained through this method act as versatile components in organic synthesis, enabling further modifications of functional groups. This method exhibits a wide substrate scope, employs straightforward and cost-effective reagents, eliminates the need for acidic, carbodiimide or other coupling agents, and operates at ambient temperature. Moreover, this methodology has been successfully applied to the synthesis of two natural products, Thunberginols A and F.

Scalable and sustainable reductive amidation of nitroarenes, nitroalkenes, and nitroalkyls with acyl saccharins in aqueous media - Khamkar, Sunil L.; Mohan, Rayala; Santhosh, J.; Shinde, Harish M.; Handore, Kishor L.; Mohan, S. Venkata; Reddy, D. Srinivasa (Communications Chemistry, 2025)
Amide bond formation is essential in both organic and medicinal chemistry, however, most existing methods present poor ecological efficiency. Here, we report a scalable and sustainable method for synthesizing N-substituted amides from nitroarenes, nitroalkenes, nitroalkyls, and acyl saccharin in aqueous media. This atom-efficient approach avoids column chromatography, offers high yield, and is compatible with various functional groups. It is applicable to synthesize Dispyrin, a bromopyrrole alkaloid, amide-based drugs, and agrochemicals, including paracetamol, with solvent and saccharin recycling. A comprehensive Life Cycle Assessment (LCA; ISO 14044) was conducted to evaluate the environmental impacts and sustainability of nine Active Pharmaceutical Ingredients (APIs) produced via Amidation Route (AR) and Saccharin Amidation Route (SAR). The study shows SAR methods reduce carbon footprints and environmental impacts compared to AR methods, being carbon-negative and resource-efficient. Additional reductions can be achieved through saccharin recycling and the integration of renewable energy sources, demonstrating saccharin-based processes potential to minimize environmental burdens in pharmaceutical synthesis.

Stereoselective strategies for the synthesis of functionalized cis-hydrindanes in natural product synthesis - Survase, Vijayanand U.; Handore, Kishor L. (European Journal of Organic Chemistry, 2025)
The cis-hydrindane motif is a bicyclic structure commonly found in many natural products that exhibit significant biological activity. This structural feature is present in a variety of bioactive compounds, particularly terpenoids, steroids, and alkaloids, which are known for their therapeutic potential, including anti-inflammatory, antimicrobial, antiviral, and anticancer properties. Due to its prevalence and biological relevance, the cis-hydrindane framework has attracted considerable attention from synthetic chemists, who have devoted substantial effort toward developing efficient and diverse methods for constructing this important motif. Many of the synthesized cis-hydrindane compounds have been used as key intermediates or building blocks in the total synthesis of complex natural products. This review provides an overview of strategic approaches for synthesizing functionalized cis-hydrindanes and its derivatives from 2000 to the present day, focusing on their application in natural product synthesis. By examining the diverse methods and their impact on natural product synthesis, this review will underscore the enduring importance of the cis-hydrindane framework in both synthetic organic chemistry and medicinal chemistry.
Keywords: annulation; Cis-hydrindane; Diel-Alder reaction; Natural products; Total synthesis

Synthesis of Readily Modifiable Amides from Aldehydes via an Organocatalytic Approach Using a CTAB Surfactant - Akhade, Akshay M.; Rokade, Avinash D.; Handore, Kishor L. (Journal of Organic Chemistry, 2025)
A simple and efficient organocatalytic method has been developed to access ``readily modifiable'' amides, including bench-stable N-acyl saccharin and various activated amides, from aldehydes by using CTAB- t BuOOH. A wide range of aromatic and aliphatic acyl saccharin are obtained from their respective aldehydes with moderate to good yields. The approach can be similarly applied toward the formation of N-acyl imidazole, N-acyl benzimidazole, N-methoxy-N-methylamide (Weinreb amide), N-ethyl-N-phenylbenzamide, N-acyl morpholine, N-acyl valerolactam, and N-acyl caprolactam. These compounds are frequently applied as reagents in organic transformations, including acyl coupling, decarbonylative coupling, radical coupling, and coupling that is free from transition metals, enabling the synthesis of new C-C, C-N, C-O, C-S, C-P, and C-B bonds.

Metal-free direct amidation of nitroarenes with carboxylic acids - Akhade, Akshay M.; Handore, Kishor L. (Journal of Organic Chemistry, 2026)
We report a facile, metal-free protocol for the direct amidation of readily available nitroarenes and carboxylic acids. The method proceeds via in situ activation of carboxylic acids, nitro-to-amine reduction, and subsequent C-N coupling to furnish the corresponding amide bond. This transformation exhibits broad functional group tolerance and delivers the desired amides in high yields. The method's applicability is showcased through the efficient synthesis of pharmaceutically and agrochemically important amide scaffolds and rapid derivatization of drug molecules containing carboxylic acid groups.

Palladium-catalyzed annulation of acyl saccharins with norbornene via CO shuttling - Rokade, Avinash D.; Teke, Nikhil M.; Handore, Kishor L. (Organic Letters, 2026)
Palladium-catalyzed annulation presents a new approach for synthesizing indanones from readily available N-acyl saccharins and bicyclic alkenes with high yields. This reaction proceeds via cleavage of the C-H, C-C, and C-N bonds of the acyl saccharin and the rearrangement of the carbonyl moiety by decarbonylation and CO reinsertion. This transformation introduces an innovative bond disconnection strategy for annulation reactions via CO shuttling. Additionally, it can also be applied in the synthesis of the CDC7 inhibitor and ferrocene indanone.